A retrospective, naturalistic study of deep brain stimulation and vagal nerve stimulation in young patients* - Deniz Yuruk; Can Ozger; Juan F. Garzon; Paul A. Nakonezny; Jennifer L. Vande Voort; Paul E. Croarkin (Brain and Behavior, 2024)
Abstract Introduction Invasive neuromodulation interventions such as deep brain stimulation (DBS) and vagal nerve stimulation (VNS) are important treatments for movement disorders and epilepsy, but literature focused on young patients treated with DBS and VNS is limited. This retrospective study aimed to examine naturalistic outcomes of VNS and DBS treatment of epilepsy and dystonia in children, adolescents, and young adults. Methods We retrospectively assessed patient demographic and outcome data that were obtained from electronic health records. Two researchers used the Clinical Global Impression scale to retrospectively rate the severity of neurologic and psychiatric symptoms before and after patients underwent surgery to implant DBS electrodes or a VNS device. Descriptive and inferential statistics were used to examine clinical effects. Results Data from 73 patients were evaluated. Neurologic symptoms improved for patients treated with DBS and VNS (p < .001). Patients treated with DBS did not have a change in psychiatric symptoms, whereas psychiatric symptoms worsened for patients treated with VNS (p = .008). The frequency of postoperative complications did not differ between VNS and DBS groups. Conclusion Young patients may have distinct vulnerabilities for increased psychiatric symptoms during treatment with invasive neuromodulation. Child and adolescent psychiatrists should consider a more proactive approach and greater engagement with DBS and VNS teams that treat younger patients.